2010
DOI: 10.1074/jbc.m109.059832
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Glycosynthase Mutant Derived from Mucor hiemalis Endo-β-N-acetylglucosaminidase Capable of Transferring Oligosaccharide from Both Sugar Oxazoline and Natural N-Glycan

Abstract: Endo-M, an endo-␤-N-acetylglucosaminidase fromMucor hiemalis, is a family 85 glycoside hydrolase. This enzyme is unique in that it can transfer en bloc the oligosaccharide of various types of N-glycans onto different acceptors, and thereby it enzymatically generates diverse glycoconjugates. In this study, we performed mutational and kinetic studies focusing on a key catalytic asparagine 175 of Endo-M. We have shown that most of the Asn-175 mutants had significantly diminished hydrolysis activity but acted as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 31 publications
2
123
0
Order By: Relevance
“…These include a key asparagine residue for endoglycosidases Endo-A (Asn-171) (36), Endo-M (Asn-175) (37,38), and Endo-D (Asn-322) (24) of the GH85 family, or a key aspartic acid residue for the GH18 family endoglycosidases Endo-S (Asp-233) (25) and Endo-F3 (Asp-165) (32). Sequence alignment of Endo-S2 and Endo-S revealed that the Asp-184 of Endo-S2 was the residue equivalent to Asp-233 of Endo-S essential for promoting oxazolinium ion formation in hydrolysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include a key asparagine residue for endoglycosidases Endo-A (Asn-171) (36), Endo-M (Asn-175) (37,38), and Endo-D (Asn-322) (24) of the GH85 family, or a key aspartic acid residue for the GH18 family endoglycosidases Endo-S (Asp-233) (25) and Endo-F3 (Asp-165) (32). Sequence alignment of Endo-S2 and Endo-S revealed that the Asp-184 of Endo-S2 was the residue equivalent to Asp-233 of Endo-S essential for promoting oxazolinium ion formation in hydrolysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that a quantitative conversion of the Fuc␣1,6GlcNAc-CD52 (8) to the glycopeptide (9) could be achieved within 2 h when a 3-fold excess of the glycan oxazoline (7) was used, demonstrating the efficiency of the Endo-F3 D165A-catalyzed transglycosylation. We have also tested several glycosynthases described previously, including the D233A mutant of Endo-S, the N322A and N322Q mutants of Endo-D, the N175Q mutant of Endo-M, and the N171A mutant of Endo-A (29,30,(32)(33)(34). We found that none of those glycosynthases were able to transfer triantennary complex glycans from the glycan oxazoline.…”
Section: Endo-f3 Mutant D165a Is Able To Transfer Triantennary N-glycmentioning
confidence: 99%
“…We have previously generated glycosynthases from endoglycosidases of both the GH85 and GH18 family by site-directed mutation at a key residue that is responsible for promoting the formation of the oxazolinium ion intermediate during hydrolysis, which proceeds in a substrate-assisted mechanism (29,30,(32)(33)(34). These include a key asparagine residue for the GH85 endoglycosidases Endo-A (Asn-171), Endo-M (Asn-275), and Endo-D (Asn-322) or a key aspartic acid residue for the GH18 family endoglycosidase Endo-S (Asp-233).…”
Section: Generation and Characterization Of Glycosynthase Mutants Of mentioning
confidence: 99%
“…This enhanced transglycosylation activity together with its reduced product hydrolysis activity makes N175Q a valuable mutant for glycoconjugate synthesis. 57) …”
Section: Enhancement Of Transglycosylation and Glycosynthase-like Actmentioning
confidence: 99%
“…However, it was found that the rate of transglycosylation with mutant N175A was much lower than that of the wild-type Endo-M or mutant Y217F. Thus, to improve further the catalytic efficiency of the glycosynthase for practical use, we performed systematic mutagenesis at the critical Asn-175 site of Endo-M. 57) We tried to replace this residue with the other 19 natural amino acid residues, except for proline. Of these, N175Q showed extraordinarily high transglycosylation activity, with an initial rate about 9 times and 1.5 times higher than those of N175A and the wild-type enzyme respectively.…”
Section: Enhancement Of Transglycosylation and Glycosynthase-like Actmentioning
confidence: 99%